MODELAGEM MATEMÁTICA NA EDUCAÇÃO BÁSICA: UMA PROPOSTA PARA A FORMAÇÃO INICIAL DOS PROFESSORES DO MAGISTÉRIO - Bastos, Antonio Roberto (2018)
The mathematics education is permeated by various types of conceptuals knowledges, wich are investigated, analyzed and assimilated by the students in a significant way, through of diversified methodologies, aiming improvements in the quality of teaching and learning of mathematics' concepts. Among the methodological proposals that stand out, is the Mathematical Modeling, which can be discussed as a pedagogical procedure, that seeks to build a relationship that explains mathematically the day by day phenomena’s, helping in the positioning and the construction of meanings. The use of it, implies that teachers are trained in initial and continued levels, because skills to solve problems are required in a non-linear teaching. Therefore, the teacher training represents an opportunity for these professionals rethinking their practices, discussing theories, relating theoretical and practical knowledge, and sharing knowledge. Using the modeling, they can perceive the relationships established between it and other theoreticals proposals in the education's area, such the constructivist theories, which discuss the influence and relationship of environments in the cognitive structures of the subjects who learn. Thus, investigating the perspective of training in mathematical modeling, this research aimed to answer: how can a teaching methodology based in the mathematical modeling can contribute to the initial training of mathematics' teachers in the Magisterium of Education, facilitating the learning of the contents of the area and the mediation of teaching and learning processes? In order to answer this question, the mainly objective was to promoting the formation of a professionals group from the Magisterium of Basic Education for the initial years of elementary education, in the perspective of Mathematical Modeling. The methodological procedures to reach this objective, consisted in a proposal based on the modeling as a didactic procedure, with the students of the group in question. The approaches were part of the curricular components of students, named Methodology of Mathematics' Teaching, and Supervised Internship. It was mainly observed, that the learning of the mathematical contents was facilitated, that the procedures of uses of modeling were understood and that there was interest in using it in future practices. Thus, this proposal presented a possibility of change to the teaching of mathematics, based mainly on students as critical subjects, therefore, responsible and active in the assimilation of knowledge. The proposal developed, was outlined in an educational product, to facilitate the access of basic education's teachers to the methodology, in a way that they can adapt and use it according to their realities.